Síntese de sodalita em baixa temperatura a partir de rejeito de caulim - ARAÚJO, Jussane Martins (2024)
The sodalite was synthesized using as a source of silicon and aluminum kaolin waste from a mining industry located in the Amazon region, kaolin producer for the paper cover. Both the starting material and the synthesized products were characterized by X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM). The synthesis of sodalite occurred in hydrothermal conditions through the static autoclave at constant temperature of 110 ° C and varying times of 12, 20, 22 and 24 hours. The starting materials used in the synthesis were kaolin waste (in nature), NaOH solution (5N) and NaCl (1N). Still further sought to investigate the influence of the addition and non-addition of water in the reaction mixture, addition to the use of a lower synthesis temperature than those normally used in other studies, which are between 150 and 200°C. In all cycles, either with water or non composing the reaction mixture, the sodalite was formed. However, in reaction mixture containing water, besides the formation of sodalite phase, there was also the synthesis of cancrinita. In the reaction mixture without water, the sodalite was the only phase formed. Thus, it was found that the time has not had a strong influence on the synthesis of sodalite, which was formed after 12 hours. This work also showed that it is possible to form the sodalite at a lower temperature of 110°C.